Variability of Myocardial Strain During Isometric Exercise in Subjects With and Without Heart Failure - Blum, Moritz; Hashemi, Djawid; Motzkus, Laura Astrid; Neye, Marthe; Dordevic, Aleksandar; Zieschang, Victoria; Zamani, Seyedeh Mahsa; Lapinskas, Tomas; Runte, Kilian; Kelm, Marcus; Kühne, Titus; Tahirovic, Elvis; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background: Fast strain-encoded cardiac magnetic resonance imaging (cMRI, fast-SENC) is a novel technology potentially improving characterization of heart failure (HF) patients by quantifying cardiac strain. We sought to describe the impact of isometric handgrip exercise (HG) on cardiac strain assessed by fast-SENC in HF patients and controls. Methods: Patients with stable HF and controls were examined using cMRI at rest and during HG. Left ventricular (LV) global longitudinal strain (GLS) and global circumferential (GCS) were derived from image analysis software using fast-SENC. Strain change < -0.5 and > +0.5 was classified as increase and decrease, respectively. Results: The study population comprised 72 subjects, including HF with reduced, mid-range and preserved ejection fraction and controls (HFrEF n=18 HFmrEF n=18, HFpEF n=17, controls: n=19). In controls, LV GLS remained stable in 36.8%, increased in 36.8% and decreased in 26.3% of subjects during HG. In HF subgroups, similar patterns of LV GLS response were observed (HFpEF: stable 41.2%, increase 35.3%, decrease: 23.5%; HFmrEF: stable 50.0%, increase 16.7%, decrease: 33.3%; HFrEF: stable 33.3%, increase 22.2%, decrease: 44.4%, p=0.668). Mean change between LV GLS at rest and during HG ranged close to zero with broad standard deviation in all subgroups and was not significantly different between subgroups (+1.2 ± 5.4 %, -0.6 ± 8.3 %, -1.7 ± 10.7 % and -3.1 ± 19.4 %, p=0.746 in controls, HFpEF, HFmrEF and HFrEF, respectively). However, the absolute value of LV GLS change – irrespective of increase or decrease – was significantly different between subgroups with 4.4 ± 3.2 % in controls, 5.9 ± 5.7 % in HFpEF, 6.8 ± 8.3 % in HFmrEF and 14.1 ± 13.3 % in HFrEF (p=0.005). The absolute value of LV GLS change significantly correlated with resting LVEF, NTproBNP and Minnesota Living with Heart Failure questionnaire scores. Conclusion: The response to isometric exercise in LV GLS is heterogeneous in all HF subgroups and in controls. The absolute value of LV GLS change during HG exercise is elevated in HF patients and associated with measures of HF severity. The diagnostic utility of fast-SENC strain assessment in conjunction with HG appears to be limited.